What are you going through - Nunez, Sigrid (Riverhead Books, 2020)
"A woman describes a series of encounters she has with various people in the ordinary course of her life: an ex she runs into by chance at a public forum, an Airbnb owner unsure how to interact with her guests, a stranger who seeks help comforting his elderly mother, a friend of her youth now hospitalized with terminal cancer. In each of these people the woman finds a common need: the urge to talk about themselves and to have an audience to their experiences. The narrator orchestrates this chorus of voices for the most part as a passive listener, until one of them makes an extraordinary request, drawing her into an intense and transformative experience of her own. In What Are You Going Through, Nunez brings wisdom, humor, and insight to a novel about human connection and the changing nature of relationships in our times. A surprising story about empathy and the unusual ways one person can help another through hardship, her book offers a moving and provocative portrait of the way we live now"--